KiDS-450 + 2dFLenS: Cosmological parameter constraints from weak gravitational lensing tomography and overlapping redshift-space galaxy clustering. Issue 4 (31st October 2017) - Joudaki, Shahab; Blake, Chris; Johnson, Andrew; Amon, Alexandra; Asgari, Marika; Choi, Ami; Erben, Thomas; Glazebrook, Karl; Harnois-Déraps, Joachim; Heymans, Catherine; Hildebrandt, Hendrik; Hoekstra, Henk; et al.
Abstract: We perform a combined analysis of cosmic shear tomography, galaxy–galaxy lensing tomography, and redshift-space multipole power spectra (monopole and quadrupole) using 450 deg 2 of imaging data by the Kilo Degree Survey (KiDS-450) overlapping with two spectroscopic surveys: the 2-degree Field Lensing Survey (2dFLenS) and the Baryon Oscillation Spectroscopic Survey (BOSS). We restrict the galaxy–galaxy lensing and multipole power spectrum measurements to the overlapping regions with KiDS, and self-consistently compute the full covariance between the different observables using a large suite of N -body simulations. We methodically analyse different combinations of the observables, finding that the galaxy–galaxy lensing measurements are particularly useful in improving the constraint on the intrinsic alignment amplitude, while the multipole power spectra are useful in tightening the constraints along the lensing degeneracy direction. The fully combined constraint on $S_8 \equiv σ _8 \sqrt{Ω _{\rm m}/0.3}=0.742± 0.035$, which is an improvement by 20 per cent compared to KiDS alone, corresponds to a 2.6σ discordance with Planck, and is not significantly affected by fitting to a more conservative set of scales. Given the tightening of the parameter space, we are unable to resolve the discordance with an extended cosmology that is simultaneously favoured in a model selection sense, including the sum of neutrino masses, curvature, evolving dark energy and modified gravity. The complementarity of our observables allows for constraints on modified gravity degrees of freedom that are not simultaneously bounded with either probe alone, and up to a factor of three improvement in the S 8 constraint in the extended cosmology compared to KiDS alone.